Consumption of foods containing prohibited artificial colors among middle-school children in Nay Pyi Taw union territory, Myanmar - Nwe Oo; Yu Mon Saw; Hnin Nwe Ni Aye; Zaw Zaw Aung; Hnin Nandar Kyaw; Ae Mon Tun; Tetsuyoshi Kariya; Eiko Yamamoto; Nobuyuki Hamajima (BMC, 2019)
Abstract Background Food safety control in Myanmar is regulated by the Department of Food and Drug Administration (FDA). FDA conducts food safety education programs in schools and regular market surveys of foods containing prohibited artificial colors. However, the consumption of foods containing FDA-prohibited artificial colors among school children is understudied. This study aimed to assess the consumption of foods containing FDA-prohibited artificial colors among middle-school children in Nay Pyi Taw Union Territory, Myanmar. Methods A cross-sectional study was conducted at eight public schools in Nay Pyi Taw Union Territory in 2017. The schools were selected using simple random sampling with a drawing method. In total, 776 students (359 boys and 417 girls) participated in face-to-face interviews using a structured questionnaire and photos of foods containing artificial color published by FDA. A multiple logistic regression was performed to estimate adjusted odds ratio (AOR) for consumption of such foods. Results In total, 519 (66.9%) children consumed foods with the FDA-prohibited colors. It was revealed that students at suburban schools were nearly five times more likely to consume foods containing FDA-prohibited artificial colors (AOR = 4.84; 95% confidence interval (CI) 2.99-7.82) compared to those at urban schools. In addition, being in the seventh grade (AOR = 3.38; 95% CI 2.30-4.98), availability of prohibited food in school canteen (AOR = 6.16; 95% CI 2.67-14.22), and having a less educated father (AOR = 1.76; 95% CI 1.06-2.92) were positively associated with consumption of the foods with the prohibited colors. Conclusion More than half of the students consumed foods with the prohibited colors. Consumption was more frequent among students from suburban schools, those with unsafe foods accessible at their school canteen, seventh graders, and students with a less educated father. The findings highlighted that school food safety programs, which focus on preventing consumption of foods containing FDA-prohibited artificial colors, are urgently required. Food safety regulation is also required to ban the sale of unsafe food, especially in school canteens.